2019
DOI: 10.21776/ub.jkb.2019.030.03.4
|View full text |Cite
|
Sign up to set email alerts
|

Minyak Cengkeh (Syzygium aromaticum) Menginduksi Apoptosis pada Sel Kanker Servik HeLa melalui Peningkatan Kadar Protein p53

Abstract: <p>Kanker serviks merupakan kanker yang paling sering dijumpai pada wanita setelah kanker payudara. Kanker ini terkait dengan infeksi persisten virus yaitu Human Papillomovirus (HPV). Virus ini mengekspresikan protein onkogenik virus yaitu protein E6 dan E7 yang terkait dengan proses karsinogenesis. Salah satu mekanisme onkogenik virus ini adalah pengikatan protein p53 yang menginduksi degradasi oleh protein E6, mengakibatkan efek anti-apoptosis dan proliferasi sel secara terus menerus. Minyak cengkeh ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Thus, treatments that are both more effective and less expensive are required. Permatasari et al showed that eugenol’s antitumor mechanisms trigger cell death in cancer cells via activation of p53 protein levels [ 98 ]. To evaluate the antimetastatic properties of eugenol against cervical cancer, Permatasari et al examined the effect of eugenol on cell migration.…”
Section: Eugenol Anticancer Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, treatments that are both more effective and less expensive are required. Permatasari et al showed that eugenol’s antitumor mechanisms trigger cell death in cancer cells via activation of p53 protein levels [ 98 ]. To evaluate the antimetastatic properties of eugenol against cervical cancer, Permatasari et al examined the effect of eugenol on cell migration.…”
Section: Eugenol Anticancer Propertiesmentioning
confidence: 99%
“…It had a cytotoxic influence on HeLa cells at concentrations of 50–200 μM. In particular, caspase-3 and p53 protein expression are involved in this apoptotic incidence [ 98 ]. One of eugenol’s anti-carcinogenic influences in cervical cancer was to hinder cell migration.…”
Section: Eugenol Anticancer Propertiesmentioning
confidence: 99%